2021
DOI: 10.1016/j.jid.2020.06.037
|View full text |Cite
|
Sign up to set email alerts
|

miR-19a/b and miR-20a Promote Wound Healing by Regulating the Inflammatory Response of Keratinocytes

Abstract: Persistent and impaired inflammation impedes tissue healing and is a characteristic of chronic wounds. A better understanding of the mechanisms controlling wound inflammation is needed. In this study, we show that in human wound-edge keratinocytes, the expressions of microRNA (miR)-17, miR-18a, miR-19a, miR-19b, and miR-20a, which all belong to the miR-17w92 cluster, are upregulated during wound repair. However, their levels are lower in chronic ulcers than in acute wounds at the proliferative phase. Condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…The expression of TLR1, TLR2, TLR4, TLR6, TLR9, and MyD88 has been found to be significantly upregulated in the wounds of diabetic patients compared with nondiabetic wounds [164,165]. We also show that the TLR3 protein level is elevated in the wound-edge epidermis of human diabetic foot ulcers, venous ulcers, and pressure ulcers, contributing to the increased neutrophil and macrophage infiltration in these chronic wounds [144]. A single-nucleotide polymorphism (SNP) study revealed that TLR4 and TLR9 SNPs and their haplotypes may increase the risk of impaired wound healing in type 2 diabetic patients [166,167].…”
Section: Tlrsmentioning
confidence: 53%
See 4 more Smart Citations
“…The expression of TLR1, TLR2, TLR4, TLR6, TLR9, and MyD88 has been found to be significantly upregulated in the wounds of diabetic patients compared with nondiabetic wounds [164,165]. We also show that the TLR3 protein level is elevated in the wound-edge epidermis of human diabetic foot ulcers, venous ulcers, and pressure ulcers, contributing to the increased neutrophil and macrophage infiltration in these chronic wounds [144]. A single-nucleotide polymorphism (SNP) study revealed that TLR4 and TLR9 SNPs and their haplotypes may increase the risk of impaired wound healing in type 2 diabetic patients [166,167].…”
Section: Tlrsmentioning
confidence: 53%
“…These two miRNAs promote keratinocyte inflammatory chemokine and cytokine production by targeting leucine rich repeat containing G protein-coupled receptor 4 (LGR4) [146]. We also showed that the levels of all miR-17∼92 cluster members, i.e., miR-17, miR-18a, miR-19a, miR-19b, and miR-20a, decreased in several types of human chronic ulcers, including pressure ulcers, venous ulcers, and diabetic foot ulcers, in comparison with normal acute wounds [144]. Moreover, miR-19a/b and miR-20a were found to reduce keratinocyte production of inflammatory chemokines and cytokines by regulating the TLR3-NF-κB signaling pathway by targeting SHC binding and spindle associated 1 (SHCBP1) and semaphorin 7A (SEMA7A) [144].…”
Section: Micrornasmentioning
confidence: 84%
See 3 more Smart Citations